Circulating microRNA panels in subjects with metabolic dysfunction-associated steatotic liver disease after following a 2-year dietary intervention - Tobaruela-Resola, Ana Luz; Riezu-Boj, José Ignacio; Milagro, Fermín I.; Mogna-Pelaez, Paola; Herrero, José I.; Elorz, Mariana; Benito-Boillos, Alberto; Tur, Josep A.; Martínez, J. Alfredo; Abete, Itziar; Zulet, María Ángeles (Journal of endocrinological investigation, 2025)
Purpose Metabolic Dysfunction-Associated Steatotic Liver Disease (MASLD) affects one-third of the global population. Despite its high prevalence, there is a lack of minimally non-invasive diagnostic methods to assess this condition. This study explores the potential of circulating microRNAs (miRNAs) as diagnostic biomarkers for MASLD after a 2-year nutritional intervention. Methods Fifty-five subjects with steatosis (MASLD group) from the Fatty Liver in Obesity (FLiO) study (NCT03183193) were analyzed at baseline and after 6, 12 and 24 months. Participants were classified into two groups: those who still had steatosis after the intervention (unhealthy group) and those in whom steatosis had disappeared (healthy group). Hepatic status was evaluated through magnetic resonance imaging (MRI), ultrasonography, elastography and serum transaminases. Circulating miRNA levels were measured by RT-PCR. Results The dietary intervention was able to modulate the expression of circulating miRNAs after 6, 12, and 24 months. Logistic regression analyses revealed that the most effective panels for diagnosing whether MASLD has disappeared after the nutritional intervention included miR15b-3p, miR126-5p and BMI (AUC 0.68) at 6 months, miR29b-3p, miR122-5p, miR151a-3p and BMI (AUC 0.85) at 12 months and miR21-5p, miR151a-3p and BMI at 24 months (AUC 0.85). Conclusions Circulating miRNAs were useful in predicting MASLD in subjects with overweight or obesity after following a weight-loss oriented nutritional intervention. These findings highlight the potential role of miRNAs in diagnosing MASLD and underscore the importance of precision nutrition in managing and determining MASLD. Clinical trial registration Trial registration number: NCT03183193 (www.clinicaltrials.gov).